Carcinogenic Etheno DNA Adducts in Alcoholic Liver Disease: Correlation with Cytochrome P‐4502E1 and Fibrosis. (19th December 2017) - Mueller, Sebastian; Peccerella, Teresa; Qin, Hua; Glassen, Katharina; Waldherr, Rüdiger; Flechtenmacher, Christa; Straub, Beate K.; Millonig, Gunda; Stickel, Felix; Bruckner, Thomas; Bartsch, Helmut; Seitz, Helmut Karl
Abstract : Background: One mechanism by which alcoholic liver disease (ALD) progresses is oxidative stress and the generation of reactive oxygen species, among others due to the induction of cytochrome P‐4502E1 (CYP2E1). Experimental data underline the key role of CYP2E1 because ALD could be partially prevented in rats by the administration of the specific CYP2E1 inhibitor chlormethiazole. As CYP2E1 is linked to the formation of carcinogenic etheno DNA adducts in ALD patients, a causal role of alcohol‐induced CYP2E1 in hepatocarcinogenesis is implicated. The purpose of this study was to investigate CYP2E1 induction in ALD, and its correlation with oxidative DNA lesions and with hepatic histology. Methods: Hepatic biopsies from 97 patients diagnosed with ALD were histologically scored for steatosis, inflammation, and fibrosis. CYP2E1 and the exocyclic etheno DNA adduct 1, N 6 ‐etheno‐2′deoxyadenosine (εdA) were determined immunohistochemically. In addition, in 42 patients, 8‐hydroxydeoxyguanosine (8‐OHdG) was also evaluated using immunohistochemistry. Results: A significant positive correlation was found between CYP2E1 and εdA ( p  < 0.0001) as well as between CYP2E1 and 8‐OHdG ( p  = 0.039). Both CYP2E1 ( p  = 0.0094) and ɛdA ( p  < 0.0001) also correlated significantly with the stage of hepatic fibrosis. Furthermore, a significant correlation between the fibrosis stage and the grade of lobular inflammation ( p  < 0.0001) was observed. However, the amount of alcohol consumed did not correlate with any of the parameters determined. Conclusions: These data suggest an important role of CYP2E1 in the generation of εdA, in the fibrotic progression of ALD, and thus in alcohol‐mediated hepatocarcinogenesis. CYP2E1 may be a target in the treatment of ALD and a potential prognostic marker for disease progression. Abstract : The induction of Cytochrome P4502E1 (CYP2E1) by chronic ethanol consumption results in the production of reactive oxygen species (ROS) which leads to lipidperoxidation and finally to the generation of carcinogenic etheno DNA‐adducts. Since the intensity of CYP2E1 induction due to alcohol correlates with hepatic fibrosis and etheno DNA‐adduct formation, CYP2E1 may be a driving force in alcohol mediated fibrogenesis and carcinogenesis. Thus, inhibition of hepatic CYP2E1 may be protective for alcoholic liver disease.